"The enemy within never did without" : German and Japanese prisoners of war at Camp Huntsville, 1942-1945 - Littlejohn, Jeffrey L., 1973-; Ford, Charles Howard, 1964- (Texas Review Press, 2015)
Camp Huntsville was one of the first and largest POW camps constructed in America during World War II. Located roughly eight miles east of Huntsville, Texas, in Walker County, the camp was built in 1942 and opened for prisoners the following year. The camp served as a model site for POW installations across the country and set a high standard for the treatment of prisoners. Between 1943 and 1945, the camp housed roughly 4,700 German POWs and experienced tense relations between incarcerated Nazi and anti-Nazi factions. Then, during the last months of the war, the American military selected Camp.